ISLAMIC DIGITAL INHERITANCE IN MALAYSIA: THE ROLE OF POLICYMAKERS (International Journal of Islamic Business, 2025)
The adoption of e-wallet in Malaysia are proliferating with 90 percent of the Malaysia actively use e-wallet, has introduced significant challenges in its inheritance. Despites the widespread adoption of e-wallet, existing e-wallet service providers policies do not address the transfer of digital assets upon the account holder's death. This will add the existing gap on billions of ringgits in unclaimed money and raises concerns about compliance with both Islamic inheritance laws and financial regulations. This study aims to examine the role of policymakers in addressing these challenges and ensuring the inheritance of e-wallet could occur. Hence, to achieve this objective, qualitative research approach including library-based research and semi-structured interviews with key stakeholders such as lawyer, estate planner and e-wallet service providers have been conducted. The findings revealed the critical role of Bank Negara Malaysia in establishing structured and legal procedural frameworks for e-wallet inheritance. Key informants emphasize the need for mandated policies, standardized procedures and enhance regulatory oversight to facilitate the proper transfer of e-wallet to the heirs. With unclaimed money reaching RM12 billion in 2024, this study highlights the urgent need for regulatory intervention and proposes a policy framework that integrates shariah principles with digital finance governance. This will endure the legal clarity, financial sustainability, and the protections of Muslims heirs’ rights in Malaysia’s evolving digital economy.